Linking organizational justice and knowledge sharing: An empirical investigation of SMEs in Vietnam - Nguyen, Thi-Trang-Nhung; Vu, Manh-Cuong; Nguyen, Thi-Nguyen-Hong; Pham, Viet-Dung; Luu, Thi-Minh-Ngoc; Hoang, Thi-Huong (Nurture, 2024)
Purpose: The current study aims to investigate the mediating role of Perceived Organizational Support (POS) and Employee Satisfaction (ES) on the relationship between Organizational Justice (OJ) and Knowledge Sharing (KS) in Vietnamese Small and Medium-sized Enterprises (SMEs). Design/Methodology/Approach: The framework and hypotheses were examined using SEM on SPSS and AMOS software to analyse the data after receiving 489 valid responses from 73 SMEs in Vietnam. Findings: Findings confirmed that OJ positively affects POS, ES and KS. POS and ES played a partly mediator role in the relationship between OJ and KS. Moreover, the relationship between POS and KS is mediated by ES. Conclusion: OJ is a crucial and persistent concern for individuals especially within modern organizations. It is one of the key factors shaping the behavior of individual employees. Furthermore, KS behavior is a significant driver of organizational competitiveness and growth. It predicts higher organizational performance, innovation capabilities and fosters a sense of enjoyment and happiness in aiding others. However, most studies have only examined the direct relationship between OJ and KS. Consequently, the methods by which leaders affect people continue to be unclear and mostly hypothetical. Thus, it becomes essential to analyze the empirical impact of OJ on KS by considering the intermediate influence of Perceived Organizational Support (POS) and Employee Satisfaction (ES). Practical Implications: This study provides knowledge about the reality of POS and ES and their mediating role in the relationship between OJ and KS which contributes to enriching the library overall and Vietnamese in particular in this subject. Contribution to the Literature: The mediating effect of POS and ES between OJ and KS is one of the initial topics to be addressed in this study focusing on SMEs.